PENGARUH EARNING PER SHARE (EPS) DAN RETURN ON ASSET (ROA) TERHADAP HARGA SAHAM PADA PT SEMEN INDONESIA TBK PERIODE 2011-2022 - Agung Widodo; Hadijah Febriana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the influence of Earning Per Share and Return on Assets on Share Prices both simultaneously and partially at PT Semen Indonesia for the 2011-2022 period. This research uses quantitative methods with a descriptive approach and the data source used is secondary data. The data analysis techniques used in this research are descriptive statistical analysis, classic assumption tests which include normality tests, multicollinearity tests, heteroscedicity tests and autocorrelation tests, multiple linear regression analysis, hypothesis testing using the statistical method T test and F test and the coefficient of determination test. Based on the results of the Earning Per Share t test, it can be seen that t_count (4.930) > t-table (2.262) with a significance level of 0.001 < 0.05 so that the hypothesis shows that H_o1 is rejected and H_a1 is accepted, meaning that the Earning Per Share variable has a positive and significant effect on Share Prices and The results of the Return On Asset t test can be seen t_(count) 1.586) < t-table (2.262) with a significance level of 0.147 > 0.05 so that the hypothesis shows that H_o1 is accepted and H_a1 is rejected, meaning that the Return On Asset variable has no effect and is not significant on Price Share. Based on the research results, it shows that F_count (12,395) > F-table (4.26) with a significance level of 0.003 < 0.05, thus H_o1 is rejected and H_a1 is accepted, meaning that simultaneously there is a significant influence between the variables Earning Per Share and Return On Assets. to the Share Price of PT Semen Indonesia Tbk. Then the coefficient of determination value for the Earning Per Share and Return On Asset variables is 73,4% so that the remaining 26,6% is influenced by other variables not examined in this research.